In search of the lost decade everyday rights in post-dictatorship Argentina - Adair, Jennifer, 1977- (University of California Press, 2020)
"In 1983, following a military dictatorship that left thousands dead and disappeared and the economy in ruins, Raul Alfonsin was elected president of Argentina on the strength of his pledge to prosecute the armed forces for their crimes and restore a measure of material well-being to Argentine lives. Food, housing, and full employment became the litmus tests of the new democracy. In Search of the Lost Decade reconsiders Argentina's transition to democracy by examining the everyday meanings of rights and the lived experience of democratic return, far beyond the ballot box and corridors of power. Beginning with promises to eliminate hunger and ending with food shortages and burning supermarkets, Jennifer Adair provides an in-depth account of the Alfonsin government's unfulfilled projects to ensure basic needs against the backdrop of a looming neoliberal world order. As it moves from the presidential palace to the streets, this original book offers a compelling reinterpretation of post-dictatorship Argentina and Latin America's so-called lost decade"--